Amylase's impact on co-digestion for enhanced biogas production from diverse food waste and napier grass - Nitthya Gunasekaran (2024)
The aim of this thesis is develop a scalable laboratory model to generate sustainable and renewable household energy from organic waste. Production of biogas can utilize high-quality organic fertilizer to improve soil properties, simultaneously reducing pollution from banana waste, onion waste, and Napier grass. This experiment highlight the pressing environmental concern of inefficient waste management in Malaysia due to increasing waste production and inadequate infrastructure and policies. In order to produce methane, the project intends employ Napier grass, onion waste, and banana waste as substrates to produce methane as fuel to make heat and light. Employ a pH meter and a drying oven to measure dry weight, total solids, and pH levels of onion waste, Napier grass, and banana waste substrates. Utilize the HABOTEST Gas Leak Detector HT601B to detect methane presence in the samples, recording a safe 20% LEL (Lower Explosive Limit) or 9999 ppm. The pH values of onion waste, Napier grass, and banana waste substrates (5.9, 6.0, and 5.2, respectively) fall within the ideal range for efficient methane production. Additionally, investigate two substrate combinations: Onion Waste mixed with Napier Grass (OW: NP) and Banana Waste mixed with Napier Grass (BW: NG), with varying ratios before and after the anaerobic codigestion process. The ratios of the mixes both prior to and following the anaerobic codigestion process are different. Isolate Pseudomonas aeruginosa, Bacillus subtilis, and Escherichia coli bacteria from onion waste, Napier grass, and banana waste, respectively, using the streaking and spread culture method on nutrient agar. Report a methane gas detector reading of 20% LEL (Lower Explosive Limit) or 9999 ppm, indicating successful methane production.